Destination attractiveness of the South Bohemian region from the viewpoint of spatial data analysis - Renata Klufová (DETUROPE, 2016)
The aim of this paper is the evaluation of the South Bohemia region's destination attractiveness. The dimensionality of data describing the chosen attractions of the area was reduced by the factor analysis into six factors which served as an input for hot spot analysis. The hot spots analysis identifies clusters of high and low values of the factors. Cluster analysis of factor served then as a tool for a typology of the South Bohemian region according to its attractiveness for tourism. The paper shows the possibilities of spatial statistics and spatial data analysis usage in the evaluation of the area attractiveness. Obtained results can be used in the decision sphere for tourism attractions planning.